(3eUWdM GdMOjK (B/s - (3GdYKjejf, eMeO Hf UGdM Hf eMeO,s 1347-1421 (3gLQjG(B.s ((3GdOeGe (B- (3GdSYhOjI (B:s (3eDSSI GdTjN eMeO Hf UGdM GdYKjejf GdNjQjI ,s, 2014)
(3jJfGhd Yde GdGSfGO hYde GdQhGjI(B.s
Keywords: (3GdMOjKs -- (3eUWdMs